New Standardized Loco-Regional Anesthesia Based for Dacryocystorhinostomy: Role for Blunt Canula Ultrassonographic Guided - Hugo C. T. Siqueira; Clarissa M. M. Stoffel de Siqueira; Marlon Miguel Bianchi de Lima; Leonardo T. C. Lins (Research Developments in Medicine and Medical Science Vol. 2, 2023)
Epiphora is a common ophthalmologic problem that frequently requires referral to an oculoplastic specialist. If the lower lacrimonasal duct is completely blocked, however, there may be mild to severe complications that necessitate surgery to provide a new drainage path. The surgical procedure used at the institutions where this study was conducted, the external dacryocystorhinostomy with silicon intubation, had better long-term results. This article presents a revision of 218 consecutive cases from December 2016 to June 2021 in two specialized centers with the same standardized surgical and anesthetic technique. In this chapter, 242 surgical prontuaries were selected, with 218 filling the inclusion criteria. 13% of patients required additional anaesthetic infusion prior to surgery, 2.7% required field anaesthetic infusion during surgery, and 6.4% required supplementary sedation, indicating a positive outcome because the number of patients with intraoperative complaints was low and overall comfort was high. After 24 hours, no patient required pain medication, according to the follow-up. This study suggests that the presented technique is feasible as an outpatient procedure with minimal, mild, and tolerable side effects.